Development of an nir sorting machine for detecting internal disorder and quality of apple fruit - Al Harbi, Eid Mohammed, 1973-; Herlina Abdul Rahim, supervisor; Fakulti Kejuruteraan Elektrik (2012)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2012